DAYA TERIMA BARUASA SUBTITUSI TEPUNG KULIT PISANG - HJ.Sukma Wati; Nadimin Nadimin; suria Suria (Jurusan Gizi Poltekkes Kemenkes Makassar, 2017)
Background: Baruasa is favored the local snacks by the people of South Sulawesi, but low in fiber. One of the high fiber foods is the banana hump. Banana hump can be processed into semi-finished materials such as banana hump flour. Banana hump flour can be substituted on the manufacture of baruasa.Objective: The purposeof this study to determine how the effect of banana hump flour substitution on the power of the baruasa receipt. This research is pre experimental research that is making baruasa with three varieties of banana hump flour substitution (10%, 20% and 30%). Hedonic test using untrained panelists are Nutrition Students of Poltekkes Makassar as many as 35 people. Analysis of hedonic test data using Anova and Tukey test with SPSS program.Results: The results showed that the preferred formula of the panelis of the color aspect is F1 of 82.85%, the smell is F1 of 88.57%, the texture of F1 is 54.29% and the sense is F1 of 80% .The test results show that there is a difference of panelist acceptance of the color aspect, Flavor and smell of banana hump flour subtitution flour with p <α value (0,05), whereas in texture aspect there is no difference of acceptance of baruasa banana hump flour with p> α (0,05).Conclusion: It was concluded that the higher concentration of banana hump flour addition was lower due to the panelist's preference for the acceptable power.Suggestion: It is recommended for further preparation, it is better to do further research on how to reduce the color of browning, as well as the smell and flavor of the banana hump flour which is rather sharp on the baruasa.Keywords: Baruasa, Banana Hump Flour, Acceptability